REFORM ELECTION MANAGEMENT BUREAUCRACY TO MAKE A DEMOCRATIC ELECTION WITH INTEGRITY IN GORONTALO CITY - Mantali, Idham; Abdussamad, Juriko (Universitas Negeri Gorontalo, 2022)
During the implementation of the election, there were a number of problems, including the problem of human resources (HR). Attention to human resource management (HRM), namely election organizers is important to do, in anticipation of improving services and success in organizing the 2024 simultaneous elections in the Gorontalo City KPU work environment. Starting from this reason, it is necessary to take several approaches in order to improve the performance of the Gorontalo City KPU. First, the indicators for holding elections in realizing democratic elections with integrity. Second, bureaucratic reform within the Gorontalo City KPU.